Pengembangan Media Pembelajaran Flashcard Materi Klasifikasi Makhluk Hidup bagi Siswa Kelas VII SMP Negeri 2 Turen - Saiful Arifin; Primadya Anantyarta (Universitas Negeri Surabaya, 2026)
This study was motivated by problems in science learning on the classification of living things which is considered abstract and complex, as well as the dominance of lecture methods which causes seventh grade students to have difficulty in distinguishing taxonomic levels. This study aims to develop a valid flashcard learning media that is appropriate to the characteristics of seventh grade junior high school students. This type of research is Research and Development (R&D) using the 4D development model (Define, Design, Develop, Disseminate). The research subjects involved material experts, media experts, 29 students and 5 science teachers of SMP Negeri 2 Turen. The data collection instrument used a validation sheet and a user response questionnaire. The results showed that the flashcard media received a score of 88,8% for media validation and 95,5% for material validation. The response rate for the readability test of the flashcard media received a score of 96% from teachers and 91,4% from students. The results indicate that the developed flashcard media is very feasible and practical to use as a supporting media to visualize the concept of classification of living things.